Synthesis, antibacterial, and antibiofilm potential of human autophagy 16 polypeptide and analogues. Issue 4 (14th May 2018) - Varnava, Kyriakos Gabriel; Reynisson, Jóhannes; Raghothama, Srinivasrao; Sarojini, Vijayalekshmi
Abstract: This work demonstrates that the human autophagy 16 polypeptide (Atg16) has antibacterial and antibiofilm potential, perturbs both Gram positive and negative bacterial membranes and subsequently also produces ROS in compromised bacteria. Engineered Atg 16 analogues containing 1‐ and 2‐naphthyl alanines showed significant enhancement of antibacterial activity and eradicated biofilms while also possessing negligible hemolysis of mouse erythrocytes. This new family of antibacterial peptides are promising candidates in the fight against bacterial biofilms, responsible for several thousand deaths annually which are predicted to rise into the millions. Abstract :